An analysis of the role played by civil society in promoting peace and tolerance in Zimbabwe: a case study of Masakhaneni projects trust in Matobo district (2009-2013) - Moyo, Nhlanhla (Midlands State University, 2017)
This dissertation is a critical examination of the role that has been played by civil society organisations in their quest to promote peace, reconciliation and democracy in Zimbabwe, the case study being Masakhaneni Projects Trust. It traces the history of politically motivated violence as far as the liberation struggle for independence. It is also through this study that I seek to expose how a violent political culture has been institutionalized in Zimbabwe’s politics as a means of attaining political objectives. I also try to examine the various peace-building initiatives by civil society organisations, their successes and limitations in fighting for a democratic Zimbabwe. It will also try and analyze the relations between the state and civil society organisations and how these relations have had a bearing on the initiatives of civil society. Finally this dissertation tries to analyze the future of civil society in Zimbabwe